Usage Evaluation of a Mobile App to Help Understand the Rehabilitation Process of Shoulder Surgery - André Luis Giusti; Sandro da Silva Reginaldo; Thiago Barbosa Caixeta; Eduardo Damaceno Chaibe; Leonardo Vieira Santos Moraes; Rodolpho Lemes de Oliveira (Revista Brasileira de Ortopedia, 2021)
Abstract Objective The present paper aims to evaluate the quality of a mobile phone application (app) designed to guide patients after shoulder surgical procedures. Methods A free and easily accessible app was developed to help patients at home. Patients were monitored for app use and adaptation before physical therapy started. At the end of 6 weeks, a qualitative questionnaire was employed to determine the usability of the app. Results In total, 97% of the respondents reported that the app was easy to download, the exercises were readily understood, and they would recommend the app. Ninety-three percent of the participants agreed that the app made them feel a greater degree of participation in the treatment of their illness, while 90% considered the app self-explanatory. Conclusion The virtual platform helps the patients to understand the treatment, aiding the medical prescription of postoperative exercises to be performed at home.